Inflammation index SIRI is associated with increased all-cause and cardiovascular mortality among patients with hypertension - Zhao, Songfeng; Dong, Siyuan; Qin, Yongkai; Wang, Yutong; Zhang, Baorui; Liu, Aihua (Frontiers in Cardiovascular Medicine, 2023)
inflammatory biomarker systemic inflammatory response index (SIRI) is related with all-cause and cardiovascular (CVD) mortality, while the role of SIRI in hypertension patients is unclear. Methods: A total of 21506 participants with hypertension were recruited in the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2018. SIRI was calculated as the neutrophil count * monocyte count/lymphocyte count. Hypertension was defined according to the examination of blood pressure, prescription, and self-reported physician diagnosis. Survival status was followed through 31 December 2019. The non-linear relationship was assessed using restricted cubic spline analysis. The association of all-cause mortality with SIRI was evaluated using the Kaplan–Meier curve and the weighted Cox regression analysis. The predictive abilities were assessed with Receiver operating curve. Results: During 189063 person-years of follow-up, 5680 (26.41%) death events were documented, including 1967 (9.15%) CVD related deaths. A J-shaped association was observed between SIRI and all-cause and CVD mortality. The Kaplan-Meier curve indicated the all-cause and CVD mortality risks were higher in high SIRI quartiles compared with lower SIRI quartiles. After adjusting for all covariates, the SIRI was positively associated with the all-mortality risk with HR= 1.19 (1.15, 1.22), and CVD mortality with HR= 1.19 (1.15, 1.24). The result was robust in subgroup analysis and sensitivity analysis. Conclusion: Elevated SIRI level is associated with increased all-cause and CVD mortality among patients with hypertension. SIRI is considered as a potential inflammatory biomarker in the clinical practice. Further large-scale cohort studies are required to confirm our findings.